Multi-utility of therapeutic drug monitoring in inflammatory bowel diseases - Martins, Camilla de Almeida; Garcia, Karoline Soares; Queiroz, Natália Sousa Freita (Frontiers in Medicine, 2022)
Inflammatory bowel disease (IBD) treatment targets have progressed over time from clinical response to clinical and endoscopic remission. Several data have shown a positive correlation between serum biologic drug concentrations and favorable therapeutic outcomes. Therapeutic drug monitoring (TDM) has evolved as an important approach for optimizing the use of immunobiologics, especially antitumor necrosis factor therapy, in patients with IBD. The use of TDM is supported by medical societies and IBD experts in different contexts; however, challenges remain due to knowledge gaps that limit the widespread use of it. The aim of this review is to assess the role of TDM in IBD, focusing on the implementation of this strategy in different scenarios and demonstrating the multi-utility aspects of this approach in clinical practice.